Mechanical properties and hydration mechanism of super-sulfated cement prepared with ordinary Portland cement, carbide slag, and sodium silicate - Qi, Guangzheng; Zhang, Qiang; Sun, Zhengning (Frontiers in Materials, 2024)
Super-sulfated cement (SSC) is known for its low-carbon footprint, energy efficiency, and eco-friendliness (mainly derived from industrial by-products) with promising applications. However, SSC’s slow early strength development results in inadequate initial hardening, compromising its durability and limiting its use in practical engineering projects. This study aims to enhance SSC’s early performance by incorporating ordinary Portland cement (OPC), carbide slag (CS), and sodium silicate as alkaline activators alongside anhydrite. The effects of varying proportions of OPC, CS, and sodium silicate on SSC’s compressive strength and hydration mechanism have been investigated experimentally in this study. Results show that using 2% OPC, 2% CS, and 1% sodium silicate as alkaline activators effectively activates slag hydration in SSC-2, achieving a compressive strength of 9.6 MPa at 1 day of hydration. As hydration progresses, SSC’s compressive strength continues to increase. In the early hydration stage, OPC and CS create an alkaline environment for SSC, facilitating rapid slag reaction with anhydrite and sodium silicate, resulting in ettringite and C–S–H formation. Simultaneously, slag hydration produces C–S–H and OH-hydrotalcite, filling voids in the ettringite-formed skeleton structure, leading to a denser microstructure and significantly enhancing SSC’s early compressive strength. From 28 to 90 days of hydration, the ettringite formation rate decreases in the SSC system, but some anhydrite remains, while C–S–H production continues to rise, further enhancing late-stage compressive strength.